1990
DOI: 10.1111/j.1365-2621.1990.tb06752.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Activity Levels in Beef: Effect of Postmortem Aging and End‐point Cooking Temperature

Abstract: While it is known that meat flavor varies as a function of end-point cooking temperature, storage time, and activity of endogenous hydrolytic enzymes, little is known about the interrelationship of these three factors with flavor. Several endogenous enzymes and proteins with potential involvement in meat flavor were investigated. The data indicate two main observations: (1) enzymes are redistributed to new intracellular compartments during postmortem aging. (2) enzyme activity is temperature dependent over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 47 publications
4
65
0
2
Order By: Relevance
“…This suggests that cooking temperature is more important than heating time in determining the concentrations of these dipeptides. These results could be due to the solubilization and liberation of these compounds at higher cooking temperatures, a variable which has a more pronounced effect than cooking time on the structural changes of meat [1,47].…”
Section: Variations Of Carnosine and Anserine Levels In Beef Broths Omentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that cooking temperature is more important than heating time in determining the concentrations of these dipeptides. These results could be due to the solubilization and liberation of these compounds at higher cooking temperatures, a variable which has a more pronounced effect than cooking time on the structural changes of meat [1,47].…”
Section: Variations Of Carnosine and Anserine Levels In Beef Broths Omentioning
confidence: 99%
“…These include free amino acids (FAAs), peptides, some organic acids, sugars, nucleotides and their metabolites [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sasaki et al [8] has already validated that the total free amino acid only leached from the muscles into cooking juice during wetheating cooking. Therefore, the increase in amount of total free amino acid at a higher ratio of SH broiler/C-hen might be due to a larger fiber density in C-hen muscle that facilitated a narrow space for proteinases to contact the binding site of protein hydrolyzation [12]. [8], who found that wet-heat cooking of pork muscles containing 1.0% NaCl had a lower amount of total free amino acid than those without NaCl supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…These results could be due to the solubilization and liberation of these compounds at higher cooking temperatures, a variable which has a 5. MEATS more pronounced effect than cooking time on the structural changes of meat (Spanier et al, 1990).…”
Section: Meatsmentioning
confidence: 95%